2014
DOI: 10.1051/0004-6361/201322486
|View full text |Cite
|
Sign up to set email alerts
|

A low-luminosity type-1 QSO sample

Abstract: Recognizing the properties of the host galaxies of quasi-stellar objects (QSOs) is essential for understanding the suspected coevolution of central supermassive black holes (BHs) and their host galaxies. Low-luminosity type-1 QSOs (LLQSOs) are ideal targets because of their small cosmological distance, which allows for a detailed structural analysis. We selected a subsample of the Hamburg/ESO survey for bright UV-excess QSOs that contains only the 99 nearest QSOs with redshift z ≤ 0.06. From this LLQSO sample,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
84
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 81 publications
19
84
4
Order By: Relevance
“…Fischer et al (2006) have observed nine galaxies from the sample with the near-infrared (NIR) spectrograph ISAAC (VLT) and find that the spectra show signs for both AGN activity and star formation. In our NIR study (Busch et al , 2014, we find that the LLQSOs do not follow published M BH −L bulge relations for inactive galaxies. A reason could be massive star formation in the circumnuclear regions.…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Fischer et al (2006) have observed nine galaxies from the sample with the near-infrared (NIR) spectrograph ISAAC (VLT) and find that the spectra show signs for both AGN activity and star formation. In our NIR study (Busch et al , 2014, we find that the LLQSOs do not follow published M BH −L bulge relations for inactive galaxies. A reason could be massive star formation in the circumnuclear regions.…”
Section: Introductioncontrasting
confidence: 63%
“…All pixels with count level below will be masked. Busch et al (2014) give more details on the fitting process and limits of 2D-decomposition. Figure 2 shows the results of the 2D-decomposition of HE 1029-1831: in the upper row, from left to right the original K-band image, the B model image, and a residual image.…”
Section: Bulge-disk Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) the observed black hole mass function (Graham et al 2007;Shankar et al 2009;Vika et al 2009;Davis et al 2014;Mutlu-Pakdil et al 2016) and Magorrian relation (Thornton et al 2008;Jiang et al 2011;Mathur et al 2012;Jiang et al 2013;Reines et al 2013;Scott et al 2013;Busch et al 2014;Sanghvi et al 2014;Yuan et al 2014) at low redshift (z 0.5);…”
Section: Galaxy and Black Hole Propertiesmentioning
confidence: 99%
“…Although the minimization algorithms are different in these packages, we assume they bring similar results of the decomposition since they have been tested and compared by different authors (e.g. Häussler et al 2007Häussler et al , 2013Kim et al 2014;Busch et al 2014). Also, each of these codes has its advantages which will be noticed further.…”
Section: The 2d Decompositionmentioning
confidence: 99%